PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PONSEL SAMSUNG PADA KARYAWAN RUMAH SAKIT DAERAH DR. DORIS SILVANUS PALANGKA RAYA - Burhanudin Burhanudin; Tasman H. Taher (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This research aims to know whether there are any effects of cultural, social, personal and psychological factors on purchase decision of Samsung brand towards the employees of Regional Hospital of Dr. Doris Sylvanus Palangka Raya. The research methodology is quantitative.The independent variables consist of cultural, social, personal and psychological factors and the dependent variables are purchase decision. The research samples consist of 104 employees in Hospital having hand phone with Samsung brand. The data collection techniques are by questionnaire and observation. The data analysis techniques are descriptive analysis and inferential analysis. To look at the effects, so the analysis used is multiple regression analysis.From the research results, it is known that partially the cultural and psychological variables provide significant effects on purchase decision of hand phone with Samsung brand on the employees of Regional Hospital of Dr. Doris Sylvanus Palangka Raya..from the regression result, it known that the social, personal and psychological variables affects positively on the purchase decision of hand phone with Samsung brand on the employees of Regional Hospital of Dr. Doris Sylvanus Palangka Raya. Meanwhile, for the cultural variable, it has negative effect on the purchase decision of hand phone with Samsung brand on the employees of Regional Hospital of Dr. Doris Sylvanus Palangka Raya.